2015
DOI: 10.1016/j.fertnstert.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enzymatic digestion and mechanical dissociation of human testicular tissues

Abstract: Medimachine dissociation of human testicular tissues is comparably fast and leads to an enrichment of SALL4-positive spermatogonia. The use of this method may therefore constitute an advantage for the establishment of human spermatogonial cell cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Therefore, we concluded that the Medimachine II approach is optimally suitable for the testis disaggregation. Our data are in strong agreement with other groups [19,69,70].…”
Section: Cell Response Of Differently Isolated Testis Cells To Cryopr...supporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, we concluded that the Medimachine II approach is optimally suitable for the testis disaggregation. Our data are in strong agreement with other groups [19,69,70].…”
Section: Cell Response Of Differently Isolated Testis Cells To Cryopr...supporting
confidence: 94%
“…As a final consideration, mechanical procedures were set for the "minimal manipulation" to avoid regulatory restrictions established by the Food and Drug Administration (FDA) in the US and worldwide, as previously stated by De Francesco and coworkers [19]. The FDA, particularly for the regenerative medicine field, considers enzymatic procedures to be "more than minimally manipulated" and have set heavy restrictions on them, while non-enzymatic methods are considered to be "minimally manipulated" by the FDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical tissue disaggregation is an efficient and time-effective alternative to enzymatic digestion. High cell numbers, viability and spermatogonial enrichment were reported after mechanical disaggregation of TT (Schneider et al ., 2015). However, the cell viability in the samples was highly variable among suspensions, suggesting the need for further optimization of this method.…”
Section: Resultsmentioning
confidence: 98%
“…To assess the characteristics of cell types in testicular tissues of trans women, immunohistochemical stainings were performed. The use of immunohistochemical markers (lutropin-choriogonadotropic hormone receptor (LHCGR), smooth muscle actin (SMA), vimentin (VIM), sal like protein 4 (SALL 4), melanoma-associated antigen 4 (MAGE A4), DEAD-box helicase 4 DDX4/VASA) revealed that the expression patterns in trans women were identical and in agreement with the staining pattern in samples from non-transgender men [48]. This finding was confirmed by others [21,22].…”
Section: Testicular Tissues and Steroidogenesis In Our Cohort Of Tmentioning
confidence: 97%